Development and evaluation of microencapsulated peony seed oil prepared by spray drying: Oxidative stability and its release behavior during in-vitro digestion. (August 2018) - Wang, Shujie; Shi, Yan; Han, Lipeng
Abstract: In the present study, peony seed oil was encapsulated using a combination of whey protein isolate, corn syrup and soy lecithin (0.75%) as wall materials by spray drying. This formulation exhibited highest encapsulation efficiency and oxidative stability and least loss of bioactive compounds. The microstructure showed the peony seed oil microcapsules formed a complete core-shell structure with smooth surface and no apparent cracks or fissures. In-vitro digestion behavior showed more than 80% of the encapsulated oil was released from microcapsules after simulated gastrointestinal digestion. Highlights: Enhanced oxidative stability of microencapsulated peony seed oil. In-vitro digestion was used to evaluate peony seed oil microcapsules digestibility. The internal structure and digestion behavior of microcapsules was observed by CLSM.